Development and In-Vitro Clinical Study of Tinidazole - Chlorhexidine Gluconate ophthalmic suspension for Treatment of Keratitis - Hiba Muaffak Salmo; Haider Kadum Abbas; Faiz I. Al- Shakarchi; Jamal Abdul-Rahman (College of Pharmacy / Mustansiriyah University, 2007)
A new model aqueous micro fine suspension of tinidazole (TND) was developed on the basis of the combination with chlorhexidine gluconate to be useful in treatment of ungal corneal infection or ulcer (fungal keratitis). In vitro clinical study for TND - chlorhexidine gluconate showed a significant antifungal activity against certain species of fungi isolated from patients with corneal ulcer . Propylene glycol (PG) was chosen because it is known as a good solubilizer , it could be used as a tonicity adjustment agent in appropriate concentration & it is nontoxic . An enhancement in the solubility of TND was achieved also by interaction with a non-ionic surfactant polysorbate 80 (Tween80) and PG. . The models prepared by using PG were showed some practical advantages over the models containing a combination of PG and non -ionic surfactant polysorbate 80 (Tween 80) , by enhancement the in vitro dissolution & releasing of TND suspension . Previous histological studies have shown that these additives used not cause eye irritation. The prepared models showed high physiological tolerance on rabbit eye. Moreover high molecular weight methylcellulose (MC) was effective to create appropriate viscosity that was maintained unchanged after heat sterilization.